Frequency of Adverse outcomes after Induction of Labor by Intracervical Catheterization with Prostaglandin Tablet in Eclamptic Patients in Mardan Medical Complex - Shahrukh; Amin, Nuzhat; Shah, Aizaz Ali; Gul, Sadiya; Arshad, Huma (Indus Journal of Bioscience Research, 2025)
Background: Eclampsia is a life-threatening hypertensive disorder complicating pregnancy and causing extensive maternal and neonatal morbidity. Induction of labour in such patients poses clinical difficulties in mode of delivery as well as neonatal outcome. Intracervical catheterization with supplementary prostaglandin therapy has been widely used, though results by this method have been sparse in local practice. Objective: To determine the frequency of adverse outcomes after induction of labour by intracervical catheterization with prostaglandin tablet in eclamptic patients in Mardan Medical Complex. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from January to July 2024 at the Department of Obstetrics and Gynaecology, Mardan Medical Complex, Mardan. Methodology: A total of 172 eclamptic women aged 18–40 years, with singleton pregnancies beyond 36 weeks of gestation, were enrolled using non-probability consecutive sampling. Labor induction was initiated with a No. 16 Foley catheter and 50 micrograms of vaginal misoprostol, with repeated doses administered as needed. The catheter was removed after 12 hours or earlier based on labor progression or fetal condition. Cesarean section and neonatal death (within 72 hours of birth) were recorded as primary outcomes. Results: The mean maternal age was 29.49 ± 6.72 years, and mean gestational age at delivery was 38.71 ± 1.68 weeks. Cesarean section occurred in 47.1% of cases, while early neonatal death was observed in 5.2%. Cesarean delivery was significantly associated with higher parity (p=0.005), while neonatal death showed a higher, though statistically non-significant, trend in older mothers and post-term pregnancies. Conclusion: Labor induction using intracervical catheterization in eclamptic patients is associated with a high rate of cesarean delivery and a modest risk of neonatal death.